Role System Control Internal In Accounting Fraud Prevention - Mustafa, Mifta; Haliah Haliah; Nirwana Nirwana (CV. AFDIFAL MAJU BERKAH, 2024)
This study aims to analyze the role and influence of the attitude of internal auditor independence and the whistleblowing system in efforts to detect fraud in various business sectors, both private companies, state-owned companies, banking, and government institutions. This study is a qualitative study using a descriptive analysis method based on literature studies based on secondary data obtained through journal articles and previous research in the period between 2018 - 2023. The results obtained from this study are that the attitude of internal auditor independence and the whistleblowing system have a significant positive effect on the ability to detect fraud. This cannot be separated from the influence of several factors that underlie the effectiveness of the implementation of the attitude of independence and the whistleblowing system, including the control environment, the length of the relationship with the client, incentives for whistleblowers, and regulations regarding whistleblower protection.